Editorial: older‐onset inflammatory bowel disease—is it time to start looking beyond a number?. Issue 7 (7th March 2018) - Taleban, S.
Abstract : Linked Content This article is linked to Mañosa et al paper. To view this paper visithttps://doi.org/10.1111/apt.14494 .